Building Students' Social Emotional Character Phase A Through Project P5 Using Alternative Planting Media - Ambawono , Gancar Pramistri; Rahayuningsih, Setiti; Iswatiningsih, Daroe; Yudistira Fardana; Khasanah, Niswatun (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to measure the impact of planting activities using alternative planting media on the development of social-emotional character of Phase A students at SD Muhammadiyah 4 Malang City. The study used a quantitative approach with a quasi-experimental design. The research sample consisted of 130 grade 1 elementary school students involved in project-based activities. The research instruments in the form of questionnaires and structured observations were used to measure the development of aspects of cooperation, creativity, responsibility, and empathy. The results of the analysis showed that 5 students were in the "starting to develop" category, 30 students were in the "developing" category, and 95 students were in the "very developed" category. These findings indicate that project-based activities that utilize alternative planting media such as hydroton and hydrogel are effective in improving students' social-emotional character. This study emphasizes the importance of project-based learning in building students' character holistically.